Cultural Policy and Everyday Experience: Urban Imagery of a Small Croatian Town - Kelemen, Petra (2008)
Varaždin is a town in the north of Croatia, which in the last decade of the 20th century began to have truly important role as an economic and cultural centre of the region. It builds its image on the narratives of a "town suitable for living", with strong cultural tradition, often condensed in the attribute of "little Vienna" ; and most recently it is defined as the most desirable Croatian town to live in. Affirmed as a town of culture, Varaždin consciously develops cultural tourism through its cultural politics, through investments in cultural manifestations, which are believed to bring to life its social urban values. The topics of this paper are: proclaimed politics of development of Varaždin, its urbanistic strategies and, especially, recent development of cultural tourism, mostly through two recognized festivals. The aim is to present the response of the users – the citizens themselves, and also the tourists who are attracted to the town by different cultural events. By approaching the meanings people derive from the town’ s politics and urban life from the stand point of cultural anthropology, this paper puts in the centre individual experience.